2021
DOI: 10.1177/15589447211060439
|View full text |Cite
|
Sign up to set email alerts
|

Using Sentiment Analysis to Understand What Patients Are Saying About Hand Surgeons Online

Abstract: Background: Physician review websites have influence on a patient’s selection of a provider. Written reviews are subjective and difficult to quantitatively analyze. Sentiment analysis of writing can quantitatively assess surgeon reviews to provide actionable feedback for surgeons to improve practice. The objective of this study is to quantitatively analyze large subset of written reviews of hand surgeons using sentiment analysis and report unbiased trends in words used to describe the reviewed surgeons and bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Age analysis determined that younger ophthalmologists received higher star ratings and sentiment analysis scores than older ophthalmologists, a fnding that was in accordance with those of Smith et al [11]. Tis trend does not appear to be unique to the feld of ophthalmology, as Tang et al found similar results among reviews of hand and spine surgeons [14,15]. However, the geographic location of practice did not yield any statistically signifcant diferences with respect to star ratings or sentiment analysis scores.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Age analysis determined that younger ophthalmologists received higher star ratings and sentiment analysis scores than older ophthalmologists, a fnding that was in accordance with those of Smith et al [11]. Tis trend does not appear to be unique to the feld of ophthalmology, as Tang et al found similar results among reviews of hand and spine surgeons [14,15]. However, the geographic location of practice did not yield any statistically signifcant diferences with respect to star ratings or sentiment analysis scores.…”
Section: Discussionsupporting
confidence: 67%
“…Te R-squared value of this model was also used to optimize the minimum number of reviews required per physician to be included in this study. Tis method in determining the exclusion criteria was also used in the studies by Tang et al [14][15][16]. Te Student's t-tests were used to evaluate relationships between gender and both sentiment analysis scores and star ratings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although natural language processing has been previously applied to quantitatively characterise online patient reviews in other fields, such as spine surgery and hand surgery, it has not been used to evaluate online reviews of otolaryngologists from physician rating websites. 12,13 The current study therefore aimed to use a natural language processing approach to analyse physician rating website reviews of otolaryngologists in the USA and quantitatively describe patients' perspectives from interactions with their physicians.…”
Section: Introductionmentioning
confidence: 99%
“…The nursing notes written by clinicians include important information on the health status of patients. Sentiment analysis, which is a technique that processes natural language, helps to identify the attitudes or impressions of clinicians to patients using computational algorithms for extracting subjective information in the written text and classifying subjective properties ( 13 ). In previous studies, nursing notes were applied in prediction model to improve the clinical outcome prediction of patients with various diseases ( 12 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%